Nunakun-gguq Ciutengqertut/They Say They Have Ears Through the Ground : Animal Essays from Southwest Alaska - Fienup-Riordan, Ann (Book collections on Project MUSE., 2020)
"Lifeways in Southwest Alaska today remains inextricably bound to the seasonal cycles of sea and land. Community members continue to hunt, fish, and make products from the life found in the rivers and sea. Based on a wealth of oral histories collected over decades of research, this book explores the ancestral relationship between Yup'ik people and the natural world of Southwest Alaska. Nunakun-gguq Ciutengqertut studies the overlapping lives of the Yup'ik with native plants, animals, and birds, and traces how these relationships transform as more Yup'ik relocate to urban areas and with the changing environment. The book is presented in bilingual format, with facing-page translations, and will be hailed as a milestone work in the anthropologicalstudy of contemporary Alaska"--